Kebijakan Arab Saudi Melakukan Intervensi Militer di Yaman dalam Perspektif Level Analisis Individu - Mustofa Zahir; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2019)
Saudi Arabia has launched military intervention in Yemen Since March 26, 2015. The military intervention resulted in a high humanitarian crisis in Yemen. Saudi Arabia has received a lot of criticism from the international community for various violations committed. This research aims to examine the causes of Saudi Arabia’s military intervention in Yemen through the individual level analysis perspective. This research examines idiosyncratic factors in Saudi Arabia's military intervention through the perspective of political psychology, more specifically the theory of narcissism-aggression. This research is an explanatory type and uses a qualitative approach. With this framework and methods, this research aims to analyze personality factors of key individuals in Saudi Arabia's military intervention in Yemen in 2015-2017. The researcher assumed that the key individual was Prince Muhammad bin Salman. The results of this research shows that the personality of Prince Muhammad bin Salman is very influential in Saudi Arabia's military intervention in Yemen. The power of Prince Muhammad bin Salman and the political conditions of Saudi Arabia when military intervention has been launched, enabled Prince Muhammad bin Salman to stop or continue Saudi Arabia's military intervention in Yemen.The narcissistic personality of Prince Muhammad bin Salman kept him from continuing Saudi Arabia’s military intervention in Yemen.